Room to breathe - Guernsey, JoAnn Bren. (New York : Clarion Books, 1986)
Seventeen-year-old Mandy often plays the helpless role with her father and boyfriend but as she becomes caught up in the social turmoil of the early 1970's, she begins to feel the need to assert her independence.
13
Keywords: Assertiveness (Psychology) -- Fiction